"A COMPARATIVE STUDY ON THE MERITS AND DEMERITS OF COMMON TEETH WHITENING METHODS" - Yusupova Mohinur Oybek qizi (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract: Teeth whitening is considered one of the most popular and widely used aesthetic treatments of modern dentistry. Everyone dreams of having a healthy and  beautiful  smile,  because  a  smile  brightens  a  person's  facial  expression  and strengthens social ties. The natural color of the teeth often changes under the influence of age, eating habits, as well as lifestyle. These color changes have caused concern for many, and interest in whitening methods has increased. Through the process of teeth whitening, stains, jaundice and other color changes on the tooth surface are eliminated or reduced, which gives an eye-pleasing white result.